Glycemic index, glycemic load, and postprandial insulin of four typical Peruvian dishes - Zarzosa-Norabuena, Edwin A. (2025)
Introduction: The glycemic index (GI) is a classification of foods based on the glycemic response they elicit in the body after consumption. Objective: To compare the glycemic index (GI), glycemic load (GL), and postprandial insulin (PI) response of four typical Peruvian dishes. Materials and methods: An experimental study was conducted with 10 adults without type 2 diabetes mellitus. The dishes evaluated were arroz con pollo (AP), tallarín rojo (TR), lomo saltado (LS), and ají de pollo (ADP), each providing the equivalent of 50 grams of available carbohydrates. Anhydrous glucose was used as the reference food. GI was calculated according to ISO 26642:2010, using capillary blood samples collected in a fasting state and at 15, 30, 45, 60, 90, and 120 minutes after food consumption. PI was measured at baseline (fasting) and then at 60 and 120 minutes. The Friedman test was used for statistical comparisons. Results: The GI of AP was 116 ± 40.1, classifying it as high GI. TR, LS, and ADP had GI values of 28.3 ± 17.5, 31.1 ± 14.5, and 38.3 ± 25.3, respectively, and were classified as low GI. The difference between the GI of AP and the other dishes was statistically significant (p<0.050). The GL of AP was 31.1 ± 14.5 (high), while the GL of TR, LS, and ADP was low (5.50 ± 3.40, 8.10 ± 3.80, and 8.70 ± 5.80, respectively). At 60 minutes, the PI level was higher after AP consumption (62.6 ± 43.7 µUI/mL) compared to the other dishes (p<0.050). At 120 minutes, the PI level remained higher for AP but the difference was not statistically significant (p = 0.272). Conclusion: Consumption of AP results in significantly higher glycemia and insulinemia compared to the other typical Peruvian dishes.